Gender Perspective in Public Policy Formulation: A Case Study of Local Government - Munna, Afzal Sayed; Darwis, Muhammad (Universitas Negeri Makassar, 2025)
The integration of gender perspectives in public policy formulation is crucial for achieving inclusive governance, yet its implementation remains inconsistent across local governments in Indonesia. Despite various regulations supporting gender mainstreaming, disparities in gender-responsive policies persist, particularly between urban and rural areas. This research aims to investigate how gender perspectives are integrated into the policy formulation process at the local government level in Indonesia, identifying the barriers and enablers of this integration. Using a qualitative case study approach, data were collected through semi-structured interviews with local policymakers, gender experts, and civil society representatives, complemented by document analysis of relevant policy documents. The study found that urban local governments, with stronger institutional capacity and greater stakeholder involvement, were more successful in integrating gender considerations. Conversely, rural areas faced significant challenges due to a lack of resources, gender-disaggregated data, and insufficient staff training. The political will of local leaders emerged as a critical factor in driving gender mainstreaming efforts. This research contributes to the understanding of gender mainstreaming by focusing on the policy formulation phase, offering insights into the practical integration of gender perspectives. However, the study’s limitations include its reliance on case study methodology and semi-structured interviews, which may not fully represent the diversity of experiences across Indonesia. Future research should explore comparative studies, evaluate the impacts of gender-sensitive policies, and investigate the role of capacity-building initiatives in fostering sustainable gender mainstreaming practices.